1997
DOI: 10.1088/0031-9155/42/4/004
|View full text |Cite
|
Sign up to set email alerts
|

Determination of average glandular dose with modern mammography units for two large groups of patients

Abstract: Until recently, for mammography Mo anode-Mo filter x-ray tube assemblies were almost exclusively used. Modern mammography units provide the possibility to employ a variety of anode-filter combinations with the aim of adapting the x-ray spectrum to compressed breast thickness and composition. The present contribution provides information on the radiation exposure of two large groups of patients (one of 1678 and one of 945 women) who were mammographed with modern x-ray equipment, and on the dosimetry necessary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
77
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 28 publications
14
77
0
1
Order By: Relevance
“…The glandularity averaged over all four centres is 32%, which is reasonably close to the values of 35% and 43% found by Klein et al (1997), but considerably smaller than the average glandularity assumed in most dosimetry protocols, i.e. 50% glandularity, e.g.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The glandularity averaged over all four centres is 32%, which is reasonably close to the values of 35% and 43% found by Klein et al (1997), but considerably smaller than the average glandularity assumed in most dosimetry protocols, i.e. 50% glandularity, e.g.…”
Section: Resultssupporting
confidence: 82%
“…The compressed breast thickness averaged over all participating women is approximately 5.82 cm. This is slightly higher than the values of 5.59 and 5.08 cm found for two groups of patients by Klein et al (1997), but in the range of values for compressed breast thickness found by Eklund et al (1993). The standard deviations of compressed breast thickness found by Klein et al (1997) Mean glandular dose values are given for each unit in table 2.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…This decrement is due to an increase in the proportion of adipose tissue in the breast. This trend is similar to that reported [14][15][16] for German, British, and Jamaican studies, respectively. Interestingly, we found that the greatest rate of change occurs after the age of 50 years whereas, [15,17] reported that the greatest rate of change occurs between the ages of 45 and 55 years.…”
Section: Breastsupporting
confidence: 90%